Effect of Disease Acceptance on Glycemic Control in Type 2 Diabetes Mellitus Patients - Muhammad Arbyanka Diontama; TA Larasati; Anisa Nuraisa Jausal; Lisiswanti, Rika (SAFE-Network, 2025)
This study aims to analyze the relationship between disease acceptance and glycemic control in patients with type 2 diabetes mellitus (T2DM). A narrative systematic review was conducted using the Preferred Reporting Items for Systematic Reviews method, identifying 929 articles from various scientific databases, including PubMed®, ScienceDirect®, Cochrane Library®, and Google Scholar®. The screening and selection process resulted in 19 relevant articles, consisting of a mix of experimental studies and observational studies, that were analyzed to evaluate the impact of disease acceptance on diabetes management and glycemic control in T2DM patients. The review findings show that higher disease acceptance is significantly associated with improved self-management, better glycemic control (with reduced HbA1c levels), and decreased levels of stress and depressive symptoms. Several acceptance-based psychological interventions, such as Acceptance and Commitment Therapy (ACT) and group education programs, were found effective in enhancing disease acceptance. These interventions also help patients achieve optimal glycemic control. These findings emphasize the importance of applying psychological approaches in the management of T2DM to support more comprehensive and sustainable disease care, ultimately improving the quality of life for T2DM patients